THE CRYSTAL STRUCTURE OF MOSKVINITE-(Y), NA2 K (Y, REE) [SI6O15], A NEW SILICATE MINERAL WITH [SI6O15] THREE-MEMBERED DOUBLE RINGS FROM THE DARA-I-PIOZ MORAINE, TIEN-SHAN MOUNTAINS, TAJIKISTAN - Sokolova E.; Hawthorne F.C.; Pautov L.A.; Agakhanov A.A. (My University, 2003)
The crystal structure of moskvinite-(Y), ideally Na2 K (Y,REE) [Si6O15], from the moraine of the Dara-i-Pioz glacier, the Alai mountain range, Tien-Shan mountains, northern Tajikistan, a 10.623(2), b 14.970(2), c 8.553(1) Å, V 1359.8(4) Å3, space group Ibmm, Z = 4, D (calc.) = 2.850 g.cm–3, has been solved by direct methods and refined to an R1 index of 1.7% based on 936 observed [| Fo | > 4σF] unique reflections collected with single-crystal diffractometer with MoKα X-radiation. Electron-microprobe analysis gave the composition Na2.06 K0.95 (Y0.77 Dy0.09 Gd0.04 Er0.04 Ho0.02 Sm0.02 Nd0.01 Tb0.01)Σ1.00 Si6 O15 based on 15 O apfu. In the crystal structure of Na2 K (Y,REE) [Si6O15], there are two tetrahedrally coordinated T sites occupied by Si with <Si–O> = 1.623 Å. The (SiO4) tetrahedra form three-membered rings, [Si3O9], that link by sharing apical vertices to form a double-ring of the form [Si6O15]. There are two [6]-coordinated sites, one occupied by (Y0.77 + REE0.23) with <(Y,REE)–O > = 2.255 Å, and the other occupied by Na with <Na–O > = 2.438 Å. There is a [10]-coordinated site occupied by K with <K–O > = 3.062 Å. The {(Y,REE)O6} and (NaO6) octahedra share common edges to form sheets parallel to (010); these sheets connect through [Si6O15] double-rings to form a framework. Channels extend along [001] and contain K. The topology of the Na2 K Y [Si6O15] framework is identical to that of synthetic Na3 Y [Si6O15], but the arrangement of the channel cations is different. The crystal structures of double-ring silicates and [Si6O18]-chain structures are discussed.
Keywords: moskvinite-(Y); Y-silicate; crystal structure; [Si6O15] double ring; Dara-i-Pioz; Tajikistan